2014
DOI: 10.1016/j.nuclphysb.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The classical Yang–Baxter equation and the associated Yangian symmetry of gauged WZW-type theories

Abstract: We construct the Lax-pair, the classical monodromy matrix and the corresponding solution of the Yang-Baxter equation, for a two-parameter deformation of the Principal chiral model for a simple group. This deformation includes as a one-parameter subset, a class of integrable gauged WZW-type theories interpolating between the WZW model and the non-Abelian T-dual of the principal chiral model. We derive in full detail the Yangian algebra using two independent methods: by computing the algebra of the non-local cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 60 publications
(114 reference statements)
1
42
0
1
Order By: Relevance
“…(3.23) and (3.24) of [52]) provided that the Poisson brackets of Lσ assume the Maillet form and the modified Yang-Baxter equation is satisfied. Our effective action (2.12) implies a canonical structure which is precisely a double copy of the two-parameter deformation of the PCM's canonical structure presented in [53]. In this work it was shown that the Maillet brackets are satisfied and an explicit solution to the modified classical Yang-Baxter equation was found (see section 3, where the parameter ρ in there is related to the level asymmetry as in eq.…”
Section: Jhep11(2017)078mentioning
confidence: 73%
“…(3.23) and (3.24) of [52]) provided that the Poisson brackets of Lσ assume the Maillet form and the modified Yang-Baxter equation is satisfied. Our effective action (2.12) implies a canonical structure which is precisely a double copy of the two-parameter deformation of the PCM's canonical structure presented in [53]. In this work it was shown that the Maillet brackets are satisfied and an explicit solution to the modified classical Yang-Baxter equation was found (see section 3, where the parameter ρ in there is related to the level asymmetry as in eq.…”
Section: Jhep11(2017)078mentioning
confidence: 73%
“…In this section we work out the r/s-Maillet form for the isotropic group case at equal and unequal levels. In the equal level case, we review the construction in [8] as a warm up for the unequal level case.…”
Section: Group Spacesmentioning
confidence: 99%
“…Then we express L 1 or equivalently A i|1 , B ± in terms of J i± . 8 We are in position to compute the Poisson brackets of L 1 and for simplicity we start with the equal level case.…”
Section: The Isotropicmentioning
confidence: 99%
“…For an earlier attempt to study higher-dimensional cases, see [19]. For integrable deformations of Wess-Zumino-Novikov-Witten models, see [20][21][22][23][24][25][26].…”
Section: Jhep03(2015)137mentioning
confidence: 99%